2021
DOI: 10.1536/ihj.20-804
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Isolation and Pacemaker Implantation in a Patient with Dextrocardia Situs Inversus

Abstract: A 70-year-old female with dextrocardia with situs inversus (DSI) totalis and inferior vena cava occlusion underwent radiofrequency catheter ablation because she had symptomatic paroxysmal atrial fibrillation (AF). Careful preoperative examination made successful pulmonary vein isolation through the left jugular vein approach. One-year later, however, AF recurred, and symptomatic sinus bradycardia or junctional bradycardia often occurred. Then, the pacemaker was implanted. We here reported a rare case of congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…There are few case reports demonstrated that patients with DSI accompanied with AF have undergone successful PVI using manual cryoballoon [ 4 ], hotballoon [ 5 ], and manual-guided RF ablation [ 6 , 7 ]. However, catheter and long sheath manipulations in manual-guided ablation are complex in cases of heart inversion, making it more difficult to achieve good catheter-to-tissue contact during PVI, especially in the left atrial ridge area [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports demonstrated that patients with DSI accompanied with AF have undergone successful PVI using manual cryoballoon [ 4 ], hotballoon [ 5 ], and manual-guided RF ablation [ 6 , 7 ]. However, catheter and long sheath manipulations in manual-guided ablation are complex in cases of heart inversion, making it more difficult to achieve good catheter-to-tissue contact during PVI, especially in the left atrial ridge area [ 8 ].…”
Section: Discussionmentioning
confidence: 99%